(3JMSjf GdbHjMs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s ((3jhSa Hf eMeO GHf Gdhcjd Gdedhj s)
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI GeG HYO MeO Gddg GdPj Ndb aEf gPG GdcJGH CdaJg hUfaJg HQSeg hTffJg hTQaJg HGSeg hChOYJg eYkG ef ZQQ GdHZGA s
(3BNQgG (B:s
(3hCeG GdfLhQ aEfgG HNhQ HQZH ajg GdPj WQb hdWa hbOe SHH daX GdHNhQ hgh GShO cQjg GdefXQ s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B189s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs